Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $h$ be the function defined by $h(x) = \int^{x^2}_0 e^{x+t} dt$ for all real numbers $x$. I've looked in Stewart and I've looked in Spivak. They both say to use the chain rule when evaluating something like this, which gives me $h'(x) = e^{x+x^2} \cdot 2x$, but apparently the true answer is $h'(x) = (2x + 1) \cdot e^{x+x^2} - e^x$.

Could somebody explain this?

share|improve this question
2  
Rewrite as $e^x\int_0^{x^2}e^t\,dt$. Use Product Rule. –  André Nicolas Nov 9 '11 at 22:41

1 Answer 1

up vote 4 down vote accepted

First, notice that $\int_0^{x^2} e^{x+t} \,dt= \int_0^{x^2} e^xe^t \,dt = e^x \int_0^{x^2} e^t\,dt$. Since we are integrating with respect to $t$, $x$ can be treated like a constant.

Next, let $u=x^2$ and $g(u)=\int_0^u e^t \,dt$.

So we have $h(x) = e^xg(x^2)$.

The derivative is $h'(x)=e^xg(x^2)+e^xg'(x^2)2x$ (using the product rule and then the chain rule on $g(x^2)$.

However, $g'(u) = e^u$ by the fundamental theorem. Therefore, $h'(x)=e^x\left(\int_0^{x^2}e^t\,dt\right)+2xe^xe^t$. Simplifying, we have $h'(x)=2xe^{x+x^2} + \int_0^{x^2} e^{x+t}\,dt$

share|improve this answer
    
Thank you! I didn't see that. –  Matt Gregory Nov 9 '11 at 23:19

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.